Covid-19 and Stock Returns: Evidence from Malaysia - Song, Saw Imm; Yazi, Erimalida; Morni, Fareiny; Janang, Jennifer Tunga (UUM Press, 2021)
The severe acute respiratory syndrome (SARS) coronavirus or Covid-19 has affected the world unprecedentedly. Malaysia is not exempted from its impact. The Malaysian government announced a nationwide lockdown in the middle of March 2020. The magnitude of the outbreak had caused panic to the public and financial panic in the stock market. This study examined the impact of Covid-19 cases and the action taken by the government through movement control orders (MCOs) and economic stimulus packages in the stock market. Event study methodology was used to assess the impact of Covid-19 on stock returns in Bursa Malaysia. Consistent with the efficient market hypothesis, the study found that during the early stages of the MCOs, the cumulative average abnormal returns (CAAR) reflected significant negative returns. However, it showed positive returns after MCO 3 and MCO 4. The results implied that the market perceived that the pandemic was under control. The study also revealed a significant relationship between CAAR and the number of cases announced, supporting the notion that in a less to a moderately free country such as Malaysia, investors showed a certain lack of trust in the number of cases reported by the authorities, and thus overreacted to the number of reported cases. The stimulus packages that were expected to stabilise the economy and society were found to be positively significant during the early stages of the MCOs.